2023
DOI: 10.3390/ijerph20042850
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pilates on Pain, Functional Disorders and Quality of Life in Patients with Chronic Low Back Pain: A Systematic Review and Meta-Analysis

Abstract: Background: Chronic low back pain (CLBP) is a common health problem. Pilates is a unique exercise therapy. This meta-analysis aims to evaluate the efficacy of Pilates on pain, functional disorders, and quality of life in patients with chronic low back pain (CLBP). Methods: PubMed, Web of Science, CNKI, VIP, Wanfang Data, CBM, EBSCO, and Embase were searched. Randomized controlled trials of Pilates in the treatment of CLBP were collected based on the inclusion and exclusion criteria. The meta-analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…In essence, the mat Pilates method does not primarily aim to induce hypertrophy, a characteristic observed in other methods utilizing load to recruit and increase muscle fiber volume [ 47 ]. The method is characterized as a complement to hypertrophy’s role in augmenting muscle mass, with mat Pilates exercises emphasizing the quality of movement over the quantity of repetitions performed [ 22 , 48 ]. Therefore, as anticipated, the intervention did not exert a substantial influence in instigating new muscle trophism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In essence, the mat Pilates method does not primarily aim to induce hypertrophy, a characteristic observed in other methods utilizing load to recruit and increase muscle fiber volume [ 47 ]. The method is characterized as a complement to hypertrophy’s role in augmenting muscle mass, with mat Pilates exercises emphasizing the quality of movement over the quantity of repetitions performed [ 22 , 48 ]. Therefore, as anticipated, the intervention did not exert a substantial influence in instigating new muscle trophism.…”
Section: Discussionmentioning
confidence: 99%
“…This process facilitates the activation of muscle satellite cells, promoting protein synthesis through molecular pathways, ultimately resulting in an increase in muscle volume, commonly referred to as hypertrophy [ 37 ]. Notably, exercises within the mat Pilates method involve motor activity, indicating the presence of mechanical stimulation at the myotendinous junction [ 22 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pharmacotherapy may lead to side effects such as constipation, nausea, and fatigue, and prolonged use of these drugs may result in a resurgence of pain upon discontinuation ( 7 ). On the other hand, physiotherapy without the incorporation of therapeutic exercise is not suitable for alleviating long-term pain and enhancing performance because it is relatively expensive and lacks active muscle contraction ( 8 ). Therefore, exercise therapy emerges as a more effective and affordable option for therapists and specialists in treating patients with NSCLBP, given its minimal harm and ease of implementation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that Pilates may be bene cial in relieving pain and improving functional impairments in individuals with CLBP. However, its impact on improving quality of life may be less pronounced (10). In another study aiming to investigate the short-term and midterm effects of Pain Neuroscience Education (PNE) combined with Manual Therapy (MT) and Home Exercise Program (HEP) on pain intensity, lumbar functional performance, disability, and movement fear in patients with CLBP, a multidimensional treatment program combining PNE, MT, and HEP was found to be more effective in improving lumbar function and reducing pain, disability, and movement fear in the short-term (4 weeks) and midterm (12 weeks) (11).…”
Section: Introductionmentioning
confidence: 99%